SENTRA PENGEMBANGAN SUTERA, DESA PISING, KABUPATEN SOPPENG - Yunianti, Andi Detti; Nuraeni, Sitti; Malina, Asmi Citra; Suhasman, . (Jurnal Dinamika Pengabdian, 2020)
Sabbeta Village ', Pising Village, Soppeng Regency is a pilot village for silk development in Soppeng Regency. Service activities undertaken are Focus Group Discussion (FGD) and training. Partners of this community service activity are the Sabbeta Village Farmers Group and the Mega Sutera Farmers Group. The purpose of the FGD is to examine the debates and challenges raised by silk farmers in developing women's relations in Pising Village. From the results of the FGD chose a number of problems to make training materials as a solution for farmers. In general, topics related to farmers are silk related to marketing, low productivity and eco print on silk fabrics. Monopoly-producing marketing makes the price of yarn produced very low. Until now, silk farmers in Soppeng Regency only produce silk yarn, while silk fabric production is in Wajo District. Low productivity because it is related to the importance and the product, especially the yarn produced, is not standard. In addition, women-only societies develop eco-print techniques on silk fabrics. The FGD was closed with a visit to the houses of the people which were used as caterpillars, seed gardens, spinning and souvenir galleries. Based on a review of the FGD results, the activities carried out were training on entrepreneurship, silkworm maintenance and eco print. The business of silkworm maintenance can be optimal if carried out in accordance with the procedure so as to produce threads that meet the standards. The maintenance of silkworms by farmers is very conventional, not in accordance with standard procedures. The results of the eco print technique were not satisfactory because the coloring was not optimal. The training provided is expected to increase their knowledge, so that it becomes a solution to the problem so far. Keywords: Sabbeta Village, Pising Village, silkworm maintenance, eco print. ABSTRAK Kampung Sabbeta’, Desa Pising, Kabupaten Soppeng merupakan kampung percontohan untuk pengembangan sutera di Kabupaten Soppeng. Kegiatan pengabdian yang dilakukan adalah Focus Group Discussion (FGD) dan pelatihan. Mitra dari kegiatan pengabdian ini, yaitu Kelompok Tani Kampung Sabbeta’ dan Kelompok Tani Mega Sutera. Tujuan dari FGD untuk mengkaji permasalahan dan kendala yang dihadapi para petani sutera dalam mengembang-kan persuteraan di Desa Pising. Dari hasil FGD dipilih beberapa masalah untuk dijadikan bahan pelatihan sebagai solusi dari permasalahan para petani. Secara umum, permasalahan yang dihadapi petani sutera terkait pemasaran, produktifitas yang rendah dan eco print di kain sutera. Pemasaran yang bersifat monopoli membuat harga benang yang dihasilkan sangat rendah. Sampai saat ini, petani-petani sutera di Kabupaten Soppeng hanya menghasilkan benang sutera, sedangkan produksi kain sutera ada di Kabupaten Wajo. Produktifitas yang rendah disebabkan karena ketergantungan akan bibit impor dan produk, khususnya benang yang dihasilkan, tidak standar. Selain itu, masyarakat khususnya para wanita mengem-bangkan teknik eco print di kain sutera. Kegiatan FGD ditutup dengan kunjungan ke rumah-rumah penduduk yang dijadikan tempat pemeliharaan ulat, kebun benih, pemintalan, dan galeri souvenir. Berdasarkan kajian dari hasil FGD, kegiatan yang dilakukan adalah pelatihan yaitu kewirausahaan, pemeliharaan ulat sutera dan eco print. Usaha pemeliharaan ulat sutera dapat optimal jika dilakukan sesuai dengan prosedur sehingga menghasilkan benang yang memenuhi standar. Pemeliharaan ulat sutera yang dilakukan petani sangat konvensional, tidak sesuai dengan prosedur standar. Hasil teknik eco print yang dikerjakan kurang memuaskan karena pewarnaan belum maksimal. Pelatihan yang diberikan diharapkan dapat meningkatkan pengetahuan mereka, sehingga menjadi solusi dari permasalahan selama ini. Kata kunci: Kampung Sabbeta’, Desa Pising, pemeliharaan ulat sutera, eco print.